Scyllitol-hexahexylether, erstes vollgesättigtes Discogen - Klaus Praefcke; Bernd Kohne; Werner Stephan; Peer Marquardt (CHIMIA)
Numerous inositol ethers have been synthesized. Among them is the hexahexyl ether (6) of sycllitol, the first fully saturated discotic liquid crystal. This hexaether 6 exhibits a stable Dho mesophase range of > 72 K. In comparison of 6 with the hexaester 7 of scyllitol, the importance of electronic interactions to the stability of the discophase is discussed briefly.